Merchandise Inventory Turnover Analysis and Accounts Receivable Turnover Against Profitability in PT. Martina Berto Tbk (MBTO) - Ekawaty, Charisma; Syahdi, Muh. Zadli; Pasae, Ranny; Sisih, Sisih; Saputri, Tiara (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Profitability is an important indicator in assessing a company's performance. Companies that are able to manage inventory turnover and receivables turnover well tend to have optimal financial performance. The purpose of this study is to determine the level of merchandise inventory turnover in increasing profitability at PT Martina Berto Tbk and to determine the turnover of receivables in increasing profitability at PT Martina Berto Tbk. The method used in this study is quantitative and descriptive analysis.This study uses secondary data obtained from financial reports published to the public for the 2021-2023 period via the official websites of the companies used as research samples. The results of this study show that The company has demonstrated improvements in inventory and accounts receivable management. This is evident in its relatively good Gross Profit Margin, although it still fluctuates annually. More efficient inventory management helps the company reduce storage costs and the risk of damage, thus maintaining a satisfactory gross profit margin